2011
DOI: 10.1088/1367-2630/13/10/103009
|View full text |Cite
|
Sign up to set email alerts
|

On the role of complex phases in the quantum statistics of weak measurements

Abstract: Weak measurements performed between quantum state preparation and post-selection result in complex values for self-adjoint operators, corresponding to complex conditional probabilities for the projections on specific eigenstates. In this paper, it is shown that the complex phases of these weak conditional probabilities describe the dynamic response of the system to unitary transformations. Quantum mechanics thus unifies the statistical overlap of different states with the dynamical structure of transformations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 28 publications
2
91
0
Order By: Relevance
“…(12) indicates that any projective measurement {| m } can have a measurement error of ε 2 (A) = 0 if the corresponding set of weak values of m are chosen for the estimatesà m . However, weak values are generally complex, and the imaginary part is usually obtained in a dynamical response of the system that is not directly connected to the quantity represented by [34,35]. Sinceà m is an estimate of the quantityÂ, it does not have an imaginary part and Eq.…”
Section: Error Free Measurementmentioning
confidence: 99%
“…(12) indicates that any projective measurement {| m } can have a measurement error of ε 2 (A) = 0 if the corresponding set of weak values of m are chosen for the estimatesà m . However, weak values are generally complex, and the imaginary part is usually obtained in a dynamical response of the system that is not directly connected to the quantity represented by [34,35]. Sinceà m is an estimate of the quantityÂ, it does not have an imaginary part and Eq.…”
Section: Error Free Measurementmentioning
confidence: 99%
“…The consistency of these results strongly suggests that the statistics of weak measurements is a fundamental element of the Hilbert space formalism. In particular, it is possible to develop a consistent explanation for weak measurement statistics in terms of complex conditional and joint probabilities [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In the following, I will take a closer look at this relation between different joint probabilities. It is shown that deterministic transformations are described by the complex conditional probabilities p(c|a, b) that also characterize weak measurement statistics [25]. Reversibility of the transformation requires that the information about a can be recovered completely from the information about c after the transformation.…”
Section: Introductionmentioning
confidence: 99%
“…It may be worth noting that dispersion effects appear as phase shifts in the frequency representation of the photon state, so that the above result can provide a prescription for the active compensation of unintended dispersion effects. In particular, it is possible to compress the pulse, corresponding to an optimization of the overlap between the photon state and the short-time pulse at t by a unitary transform conserving the frequency ω [36].…”
Section: Wavefunction Measurement and Evaluation Of Entanglementmentioning
confidence: 99%